Korupsi dan pertanggungjawaban pidana korporasi : berikut studi kasus - Yunara, Edi, 1960- (Bandung : Citra Aditya Bakti, 2005)
Corrupt practices of corporations in Indonesia ; review of the criminal provisions applied by courts in corporate crime cases
Revision of the author's thesis (S2)--Universitas Sumatera Utara
Hadiah dpd Edi Yunara Phd. Ilmu Hukum USU Medan
Includes bibliographical references (p. 135-139)
Keywords: Corporation law -- Indonesia -- Cases; Corruption -- Indonesia; Corporations -- Corrupt practices -- Indonesia; Business enterprises -- Corrupt practices -- Indonesia; Misconduct in office -- Indonesia; Trials (Misconduct in office) -- Indonesia